Plasma-combined auxiliary liquid metal self-activation method and application thereof
By combining plasma-assisted liquid metal self-activation method, the challenges of liquid metal particles in the prior art in terms of resolution and activation are solved, and a high tensile, conductive and high resolution interconnect structure is achieved, which is suitable for the manufacturing of stretchable electronic devices.
Patent Information
- Application Number
- CN202411588780.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-29
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to develop interconnect structures that can withstand large strains while maintaining low resistance, and liquid metal particles have challenges in resolution and activation, making it difficult to achieve interconnect structures with high tensileability, conductivity and high resolution.
Using a plasma-assisted liquid metal self-activation method, a plasma treatment of the patterned liquid metal photoresist is carried out, hydrophilic groups are introduced, and an elastomeric solution is poured on a micro-scale liquid metal pattern, and the elastomeric film is peeled off to enhance the adhesion and cohesion of the liquid metal nanoparticles to achieve the activation of the conductive pathway.
The high-quality micro-scale liquid metal pattern is achieved while transforming it from an insulator to a high conductor, improving conductivity and resolution, and is suitable for the manufacturing of stretchable electronic devices.
Smart Images

Figure CN119644684A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photoresists, and in particular to a plasma-assisted liquid metal self-activation method and application thereof. Background Art
[0002] Electronic systems that integrate rigid active components (such as integrated circuits) onto stretchable substrates combine bio-like mechanical properties with excellent electrical performance, and therefore have great potential in applications such as prosthetics, health monitoring, brain-computer interfaces, and intelligent robotics. A key challenge facing these systems is to develop interconnect structures that can withstand large strains while maintaining low resistance to ensure that the system can still function properly under significant deformation. Current solutions, such as structuring rigid metals into serpentine or wavy patterns or developing stretchable conductive materials, either reduce the integration density or exhibit low conductivity, thereby limiting the overall performance of the system. This highlights the need for improved interconnect designs that effectively balance mechanical flexibility, electrical performance, and integration density.
[0003] Gallium-based liquid metals (LMs) offer great potential for stretchable electronic devices due to their unlimited deformability and metal-like conductivity. However, their inherent fluidity and high surface tension pose challenges for deposition and high-resolution patterning, which usually require complex techniques such as selective wetting or imprinting. Although LM particles with spontaneously formed oxide layers improve solution processability, they still exhibit relatively low levels of resolution, typically ranging from tens to hundreds of microns. This limitation stems not only from the resolution limitations of conventional patterning techniques such as screen printing, but more importantly, it is difficult to activate smaller LM particles, which is crucial to obtain finer patterns.
[0004] Achieving high conductivity in LM particles involves disrupting their non-conductive oxide shell to allow fusion of the metallic core. Conventional activation methods, such as mechanical force, laser ablation, or ultrasonic treatment, typically require harsh conditions and exhibit limited effectiveness over large areas due to the uniform distribution of the force across all particles. The challenge becomes more severe as particle size decreases, as the required activation force increases with smaller particle size. Therefore, the lack of effective and scalable patterning and activation strategies for nanoscale LM particles remains a significant obstacle to the development of interconnected structures that combine high stretchability, conductivity, and high resolution. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for plasma-assisted liquid metal self-activation, comprising the following steps: S1, preparing a patterned liquid metal photoresist on a silicon substrate; S2, plasma treating the patterned liquid metal photoresist; S3, pouring the elastomer solution on the silicon base; S4, evaporating the solvent in the elastomer solution to obtain an elastomer film; S5. Peeling the elastomer film off the silicon substrate to obtain a liquid metal conductive pattern attached to the elastomer film.
[0006] Optionally, in step S2, the patterned liquid metal photoresist is placed in an air environment plasma cleaning machine for plasma treatment, the power of the air environment plasma cleaning machine is above 100 W, and the plasma treatment time is above 2 seconds.
[0007] Optionally, the power of the air environment plasma cleaning machine is 100-200 W, and the plasma treatment time is 10 seconds to 40 seconds.
[0008] Optionally, step S1 includes: S11, preparing ligand-modified liquid metal nanoparticles: mixing liquid metal and ligand in a solvent, and then performing a first ultrasonic treatment to obtain ligand-modified liquid metal nanoparticles, wherein the liquid metal includes gallium or a gallium-based alloy, and the ligand includes at least one of amphiphilic polymers; S12, adding a photosensitive crosslinking agent and a solvent to the ligand-modified liquid metal nanoparticles, and then uniformly mixing them by a second ultrasonic method to obtain a liquid metal photoresist composition; S13, monolayer modification on silicon substrate; S14, spin coating the liquid metal photoresist composition obtained in step S12 on the substrate to obtain a liquid metal nanoparticle film; S15, exposing the liquid metal nanoparticle film; S16, developing the liquid metal nanoparticle film in a developer, and drying to obtain a patterned liquid metal photoresist.
[0009] Optionally, in step S11, the mass ratio of liquid metal: amphiphilic polymer is no more than 100:6; in step S12, the final mass ratio of amphiphilic polymer modified liquid metal nanoparticles: photosensitive crosslinker: solvent is 100:5-40:500-2000; in step S15, the liquid metal nanoparticle film is exposed by a maskless laser direct writing system.
[0010] Optionally, the molar ratio of the hydrophilic structural unit to the lipophilic structural unit in the amphiphilic polymer is (0.001-0.1):1; the photosensitive crosslinker includes at least one of a double-ended bis-aziridine crosslinker, a double-ended perfluoroazide crosslinker, and a double-ended substituted benzophenone crosslinker; and the solvent includes at least one of hydrocarbons, ketones, alcohols, ethers, and alkylamides.
[0011] Optionally, the amphiphilic polymer includes at least one of polymethyl methacrylate-polyacrylic acid, polymethyl methacrylate-polymethacrylic acid, hydrophilically modified styrene-isoprene-styrene block copolymer, hydrophilically modified styrene-butadiene-styrene block copolymer, polypropylene-polyacrylic acid, polyethylene-polyacrylic acid, polyethylene glycol-polystyrene, polyvinyl alcohol-polypropylene, polyethylene glycol-polypropylene, and polyvinyl alcohol-polystyrene; and / or, The photosensitive crosslinking agent molecule has photo-crosslinking group molecules at both ends, and the photo-crosslinking groups at both ends include at least one of an azido group, a diaziridine group, and a benzophenone group.
[0012] Optionally, in step S11, the first ultrasound duration is 15 min-360 min; and / or In step S11, the ultrasonic power of the first ultrasound is 280W-330W; and / or In step S11, the first ultrasound is performed at a temperature of -10°C to 0°C; and / or In step S12, the second ultrasound duration is 10 s-60 s; and / or In step S12, the ultrasonic power of the second ultrasound is 100 W-150 W; and / or In step S12, the second ultrasound is performed at a temperature of 0°C to 25°C.
[0013] In a second aspect, the present invention provides an application of the plasma-assisted liquid metal self-activation method provided in the first aspect in the manufacture of stretchable electronic devices or stretchable electronic systems.
[0014] Compared with the prior art, the technical solution of the present invention has the following advantages: 1. In the plasma-assisted liquid metal self-activation method provided by the present invention, hydrophilic groups are introduced into the liquid metal nanoparticles and the silicon base by plasma treatment of the patterned liquid metal photoresist, and then the elastomer solution is directly poured on the micro-scale liquid metal pattern. While peeling the elastomer film from the silicon base, due to the interaction of the hydrophilic groups, the adhesion and cohesion between the liquid metal nanoparticles and the silicon base and between the liquid metal nanoparticles and the particles are enhanced, so that the local stress concentration is enhanced, and it is easier to make the discrete particles break and fuse to form a conductive path (this process is referred to as "activation" in this article). This process maintains the high quality of the micro-scale liquid metal pattern defined by lithography, while transforming it from an insulator to a high conductor.
[0015] 2. In the plasma-assisted liquid metal self-activation method provided by the present invention, the liquid metal photoresist composition used has a simple formula, and only needs to disperse the ligand-modified liquid metal nanoparticles and the photosensitive cross-linking agent together in a solvent. Compared with the liquid metal photoresist in the prior art which requires up to 6 components (the liquid metal photoresist currently reported usually includes at least 6 components: photoinitiator; photosensitizer, photoacid generator, photoresist resin, active diluent (or monomer), and auxiliary agent), the composition has been greatly simplified.
[0016] 3. In the combined plasma-assisted liquid metal self-activation method provided by the present invention, the liquid metal photoresist composition includes 60 wt%-95 wt% of ligand-modified liquid metal nanoparticles and 5 wt%-40 wt% of photosensitive crosslinking agent according to the mass of the solute. This formula greatly improves the mass proportion of liquid metal nanoparticles in the system, which means that the proportion of conductive materials in the photoresist increases, thereby improving conductivity. In addition, in the present invention, the surface of the liquid metal nanoparticles is coated with a nanoshell, which produces good confinement and protection for the liquid metal nanoparticles, greatly preventing particle agglomeration, making it stably dispersed in the solvent, giving the photoresist good liquid phase processing ability, and can have good film density, film adhesion, subsequent photolithography accuracy and other properties when the conductive material content is very high.
[0017] 4. In the combined plasma-assisted liquid metal self-activation method provided by the present invention, a chemical basis for high-resolution photolithography patterning is formed through a light-induced colloidal solubility adjustment design. Specifically, the liquid metal photoresist composition includes liquid metal nanoparticles wrapped by an amphiphilic polymer (such as an amphiphilic block copolymer) and a photosensitive crosslinker. The photosensitive crosslinker promotes changes in solubility by initiating crosslinking by UV light (ultraviolet light) during the patterning process. The amphiphilic polymer acts as a surfactant to stabilize the liquid metal nanoparticles in a solvent (such as a non-polar organic solvent-toluene) and also as a crosslinking site for reacting with the photosensitive crosslinker. The hydrophilic groups in the amphiphilic polymer are anchored on the oxide shell of the liquid metal nanoparticles through coordination, while the hydrophobic groups in the amphiphilic polymer prevent particle agglomeration through steric barriers, thereby promoting changes in solubility, which is beneficial to further realize dense liquid metal nanoparticle photolithography patterning.
[0018] 5. In the combined plasma-assisted liquid metal self-activation method provided by the present invention, liquid metal nanoparticles with a size range of about 200 nanometers to about 1 micron are synthesized by adjusting process parameters such as ultrasonic time and ultrasonic power, wherein the combination of the amphiphilic polymer as a surfactant and the reduced size of the liquid metal nanoparticles reduces the surface tension. In the subsequent processing process, even on a modified silicon material wafer (such as modified with octadecyltrichlorosilane (OTS)), a uniform liquid metal nanoparticle film can be formed by simple solution processing without the need for wetting metal or complex printing equipment.
[0019] In the patterning process of liquid metal photoresist, under ultraviolet light irradiation, a ligand containing an amphiphilic polymer is inserted through X-H (X=C, N), and taking a double-end substituted diazirine cross-linking agent as an example, the carbon carbene generated at both ends of the diazirine molecule can effectively connect the liquid metal nanoparticles to form a metal particle cross-linking network, reduce the colloid solubility, and spontaneously enhance its adhesion to the substrate. Therefore, in the patterning method of the liquid metal photoresist of the present invention, after solvent development, the cross-linked liquid metal nanoparticle network is retained, and the dispersed liquid metal nanoparticles are redistributed to form a liquid metal pattern with a resolution of up to 2 microns, which is due to the size of the liquid metal nanoparticles reduced to the submicron level and the high spatial resolution of the lithography. Complex micro patterns are accurately replicated from the designed mask file to the liquid metal film, demonstrating the excellent patterning ability of the liquid metal photoresist.
[0020] The liquid metal photoresist composition and the preparation method thereof of the present invention have very important application value. It should be noted that the application of the liquid metal photoresist composition or the preparation method of the liquid metal photoresist composition described in the present invention in the manufacture of stretchable electronic devices or stretchable electronic systems is only a common application case, but the present invention is not limited thereto, and the liquid metal photoresist composition and the preparation method thereof of the present invention can be applied to any other suitable case.
[0021] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] FIG1 shows the ligand-modified liquid metal nanoparticles of the present invention; Figure 2 The patterned liquid metal photoresist of the present invention is shown; Figure 3 The plasma activated fusion of liquid metal nanoparticles in the present invention is shown; Figure 4 The liquid metal photoresist photolithography patterning process of the present invention is shown; Figure 5 shows the results of infrared Fourier transform spectroscopy analysis; Figure 6 The minimum line width test diagram after the liquid metal photoresist patterning of the present invention is shown; Figure 7 The invention shows the preparation of complex patterns using the liquid metal photoresist patterning method; Figure 8 The effect of photosensitive cross-linker ratio and exposure metering on pattern quality (line spacing) is shown; Fig. 9 The effect of particle size on pattern quality (line spacing) under the influence of the first ultrasound time is shown; Fig.10 The effect of substrate wettability on pattern quality (line spacing) is shown; Fig.11 A schematic diagram of plasma-assisted liquid metal activation in the present invention is shown; Fig.12 A comparison of the patterns before and after plasma activated fusion is shown, with the pattern conducting after activation; Fig.13 The conductivity of the pattern after plasma-activated fusion is shown; Fig.14 The uniformity of the activated conductivity in the area of 5 cm × 5 cm is shown; Fig.15The activation results using different elastomers are shown (SG80A, SG85A, H1221, H1052, H1062 and 126S are models of various elastomer materials); Fig.16 The XPS spectrum analysis results are shown; Fig.17 180° peel test results are shown; Fig.18 The finite element analysis (FEA) simulation results are shown; Fig.19 The finite element analysis (FEA) simulation of the changes in stress concentration caused by enhanced adhesion is shown; Fig. 20 The tensile capacity test results are shown. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and beneficial effects of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described in the following embodiments of the present invention are only exemplary descriptions of the specific embodiments of the present invention, and are intended to be used to explain the present invention, but do not constitute a limitation of the present invention.
[0024] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0025] It should be noted that, in the present invention, specific values can vary within ±2% as the numerical protection range of the present application. In addition, in the present invention, the meaning of the descriptions such as "about" or "approximately" before a numerical value means that the numerical value can be used as the numerical protection range of the present application within a variation of ±2%.
[0026] In the description of the present application, unless otherwise specified, “plurality” and similar terms mean two or more than two.
[0027] Electronic systems that integrate rigid active components (such as integrated circuits) onto stretchable substrates combine bio-like mechanical properties with excellent electrical performance, and therefore have great potential in applications such as prosthetics, health monitoring, brain-computer interfaces, and intelligent robotics. A key challenge facing these systems is to develop interconnect structures that can withstand large strains while maintaining low resistance to ensure that the system can still function properly under significant deformation. Current solutions, such as structuring rigid metals into serpentine or wavy patterns or developing stretchable conductive materials, either reduce the integration density or exhibit low conductivity, thereby limiting the overall performance of the system. This highlights the need for improved interconnect designs that effectively balance mechanical flexibility, electrical performance, and integration density.
[0028] Gallium-based liquid metals (LMs) offer great potential for stretchable electronic devices due to their unlimited deformability and metal-like conductivity. However, their inherent fluidity and high surface tension pose challenges for deposition and high-resolution patterning, which usually require complex techniques such as selective wetting or imprinting. Although LM particles with spontaneously formed oxide layers improve solution processability, they still exhibit relatively low levels of resolution, typically ranging from tens to hundreds of microns. This limitation stems not only from the resolution limitations of conventional patterning techniques such as screen printing, but more importantly, it is difficult to activate smaller LM particles, which is crucial to obtain finer patterns.
[0029] Achieving high conductivity in LM particles involves disrupting their non-conductive oxide shell to allow fusion of the metallic core. Conventional activation methods, such as mechanical force, laser ablation, or ultrasonic treatment, typically require harsh conditions and exhibit limited effectiveness over large areas due to the uniform distribution of the force across all particles. The challenge becomes more severe as particle size decreases, as the required activation force increases with smaller particle size. Therefore, the lack of effective and scalable patterning and activation strategies for nanoscale LM particles remains a significant obstacle to the development of interconnected structures that combine high stretchability, conductivity, and high resolution.
[0030] To this end, the present invention firstly proposes a liquid metal photoresist composition and a preparation method thereof, as well as a patterning method based on the liquid metal photoresist composition.
[0031] The present invention further proposes a method for combining plasma-assisted liquid metal self-activation (hereinafter referred to as PLASMA, PLASMA stands for Plasma-Assisted Activation Strategy for Liquid Metal), and the liquid metal conductive pattern prepared based on this method is used to manufacture a highly conductive, micron-scale stretchable interconnect structure. In this article, activation refers to the fusion of discrete liquid metal particles to form a conductive whole.
[0032] The liquid metal photoresist proposed in the present invention utilizes the photo-initiated covalent bonds between ligand polymers on the surface of liquid metal nanoparticles (LMNPs), promoting the photolithographic patterning of dense liquid metal nanoparticles. The combined plasma-assisted liquid metal self-activation (PLASMA) method proposed in the present invention utilizes plasma treatment to enhance the cohesion and adhesion between liquid metal nanoparticles in the photoresist, thereby making it easy to be activated and fused by external forces to form a conductive liquid metal pattern. This method is a significant improvement over previous activation methods based on external stimuli. The combination of these patterning and activation strategies supports wafer-level scalable manufacturing of stretchable interconnect structures of arbitrary shapes, greatly simplifying the production of stretchable electronic systems.
[0033] In this article, FIG1 shows the ligand-modified liquid metal nanoparticles of the present invention; Figure 2 The patterned liquid metal photoresist of the present invention is shown; Figure 3 The plasma activated fusion of liquid metal nanoparticles in the present invention is shown; Figure 4 The liquid metal photoresist photolithography patterning process of the present invention is shown; Figure 5 shows the results of infrared Fourier transform spectroscopy analysis; Figure 6 The minimum line width test diagram after the liquid metal photoresist patterning of the present invention is shown; Figure 7 The invention shows the preparation of complex patterns using the liquid metal photoresist patterning method; Figure 8 The effect of photosensitive cross-linker ratio and exposure metering on pattern quality (line spacing) is shown; Fig. 9 The effect of particle size on pattern quality (line spacing) under the influence of the first ultrasound time is shown; Fig.10 The effect of substrate wettability on pattern quality (line spacing) is shown; Fig.11 A schematic diagram of the plasma-assisted liquid metal self-activation process in the present invention is shown; Fig.12 A comparison of the patterns before and after plasma activated fusion is shown, with the pattern conducting after activation; Fig.13 The conductivity of the pattern after plasma-activated fusion is shown; Fig.14 The uniformity of the activated conductivity in the area of 5 cm × 5 cm is shown; Fig.15 The activation results using different elastomers are shown (SG80A, SG85A, H1221, H1052, H1062 and 126S are models of various elastomer materials); Fig.16 The XPS spectrum analysis results are shown; Fig.17 180° peel test results are shown; Fig.18 The finite element analysis (FEA) simulation results are shown; Fig.19 The finite element analysis (FEA) simulation of the changes in stress concentration caused by enhanced adhesion is shown; Fig. 20 The tensile capacity test results are shown.
[0034] In the present invention, the liquid metal photoresist is designed by photoinduced colloidal solubility regulation to form the chemical basis of high-resolution photolithography patterning. Specifically, in the present invention, the liquid metal photoresist composition includes ligand-modified liquid metal (LM) nanoparticles and a photosensitive crosslinker, the liquid metal includes gallium or a gallium-based alloy, and the ligand that modifies the liquid metal includes: at least one of the amphiphilic polymers. The amphiphilic polymer can be a random copolymer or a block copolymer. In some embodiments, the liquid metal photoresist is composed of liquid metal (LM) nanoparticles wrapped in a block copolymer and a photosensitive crosslinker (for example, a double-end substituted diaziridine crosslinker), which promotes changes in solubility by initiating crosslinking through ultraviolet light. The block copolymer PMAA-b-PMMA (PMAA-b-PMMA refers to a block copolymer composed of two parts, PMAA and PMMA. PMAA is poly(acrylic acid) (Poly(Methacrylic Acid)), which is a hydrophilic polymer with good water solubility, and PMMA is poly(Methyl Methacrylate) (Poly(Methyl Methacrylate)), which is a commonly used transparent plastic with good moldability and weather resistance) acts as a surfactant to stabilize liquid metal nanoparticles in non-polar organic solvents (such as toluene), and also as a cross-linking site for reaction with photosensitive cross-linkers. The hydrophilic group (also referred to as the hydrophilic structural unit elsewhere in this article) PMAA is anchored to the oxide shell of the liquid metal nanoparticles through coordination, while the hydrophobic group PMMA prevents particle agglomeration through steric hindrance. Liquid metal nanoparticles with a size range of about 200 nanometers to about 1 micron (such as Figure 1 The combination of surfactant block copolymers and reduced liquid metal nanoparticle size reduces the surface tension of liquid metal nanoparticles, allowing the formation of uniform liquid metal nanoparticle films by simple solution processing even on octadecyltrichlorosilane (OTS)-modified silicon dioxide (SiO2) wafers without the need for wetting metals or complex printing equipment.
[0035] Under ultraviolet light, such as Fourier transform infrared spectroscopy (FTIR) ( Figure 2), by inserting X-H (X=C, O) into the polymer ligand, the carbon carbenes generated at both ends of the diazirine molecule effectively connect the liquid metal nanoparticles, significantly increase the size of the liquid metal nanoparticles, reduce the colloidal solubility, and spontaneously enhance its adhesion to the substrate. Therefore, after solvent development, the cross-linked liquid metal nanoparticle network is retained, while the dispersed liquid metal nanoparticles are redistributed to form a liquid metal pattern with a resolution of up to 2 microns, thanks to the size reduction of the liquid metal nanoparticles to the submicron level and the high spatial resolution of lithography ( Figure 3 ). Complex micropatterns were accurately replicated from the designed mask file to the liquid metal film, demonstrating the excellent patterning capabilities of liquid metal photoresists.
[0036] The inventors have found that high-quality and high-resolution liquid metal patterns can be obtained when the following two criteria are met simultaneously: i) A significant solubility change from discrete nanoparticles to nanoparticle networks; ii) Controlled adhesion between the nanoparticle network and the substrate.
[0037] To further investigate these mechanisms, the inventors systematically varied substrate surface energy, nanoparticle size, photosensitive cross-linker concentration, and irradiation intensity, with the periodic line width as the evaluation parameter.
[0038] The inventors found that the substrate surface energy plays a key role in regulating the adhesion of liquid metal nanoparticles. For example, due to the strong coordination between the hydrophilic groups and the oxidized surface, the liquid metal nanoparticle film wrapped by the block copolymer is firmly adhered to the silicon dioxide (SiO2) substrate. Therefore, although the non-cross-linked liquid metal nanoparticles are soluble in the developer solvent, they are difficult to completely remove and will remain on the substrate, affecting the quality of the microscale liquid metal pattern. To solve this problem, the inventors used a monolayer of octadecyltrichlorosilane (OTS) to reduce the surface energy of the substrate and promote the removal of non-cross-linked liquid metal nanoparticles, and further adjusted the surface energy by extending the alkaline vapor treatment time. The surface energy was reduced, which was manifested as an increase in the contact angle ( Fig.10 ).like Fig.10 As shown, the pattern resolution initially improves and then stabilizes with increasing contact angle. In addition, denser octadecyltrichlorosilane (OTS) packing contributes to denser liquid metal nanoparticle packing in the colloidal film, as assessed by porosity.
[0039] The inventors also found that liquid metal nanoparticles with different particle size distributions were prepared by controlling the ultrasonic time (the "ultrasonic time" here refers to the time of the first ultrasonic in step 1 of the preparation method of the liquid metal photoresist composition). Longer ultrasonic time leads to a narrower particle size distribution and a smaller average particle size, with the minimum reaching 190nm (ultrasonic for 6 hours). The inventors found that the patterns prepared by smaller liquid metal nanoparticles have clearer edges and smaller minimum line widths (2 microns) than those prepared by larger liquid metal nanoparticles, and these patterns maintain narrow lines. The patterns prepared by larger liquid metal nanoparticles are more easily peeled off from the substrate, resulting in poor pattern resolution. In addition to the ultrasonic time, the block copolymer concentration also affects the particle size distribution and network adhesion. Although the average particle size does not change significantly (about 400±50 nanometers) when the block copolymer concentration exceeds 0.8 wt% liquid metal, increasing the block copolymer content to 5wt% will enhance the interaction between the particles and the substrate, but leave a non-negligible residue after development due to excessive adhesion.
[0040] The inventors also found that the control of photosensitive crosslinker concentration and irradiation intensity affects the pattern resolution: i) Solubility differences through covalent bonding; ii) The adhesion between the particles and the substrate was controlled by covalent anchoring of the ligands to the octadecyltrichlorosilane (OTS)-modified substrate before and after light irradiation.
[0041] The photosensitive crosslinker concentration sets an upper limit on the number of crosslinking and anchoring sites, while the irradiation intensity determines the percentage of these sites that are actually formed under ultraviolet (UV) irradiation. When one parameter is fixed, the line width decreases as the other parameter increases. Notably, at a photosensitive crosslinker concentration of 80 wt% liquid metal, a minimum line width of 5 microns was achieved with only 1000 mJ / cm² of exposure. Similarly, at an irradiation intensity of 4000 mJ / cm², the minimum line width was achieved regardless of the crosslinker concentration. These results emphasize the necessity of sufficient and saturated crosslinking of the liquid metal nanoparticle network to resist dissolution by the developer solvent.
[0042] Plasma-Assisted Liquid Metal Self-Activation (PLASMA)Because the fracture force threshold is inversely proportional to the square of the particle diameter, previously reported activation methods based on external stimuli are only effective for micron-sized liquid metal nanoparticles, but not for nanoscale particles.To address this problem, the inventors proposed to utilize intrinsic molecular-level interactions, including cohesive forces and interfacial adhesion forces between particles, combined with a concentrated force field, to achieve large-area uniform activation of nanoscale liquid metal nanoparticles without the need for external forces.
[0043] The steps of plasma assisted liquid metal self-activation (PLASMA) are Fig.11The present invention is summarized in the following. First, the photolithographically patterned liquid metal photoresist is treated with atmospheric plasma (preferably for 10 to 40 seconds) to introduce hydrophilic groups into the liquid metal nanoparticles and the substrate, and then the elastomer solution is cured directly on the microscale liquid metal pattern. While peeling the elastomer film from the substrate, the adhesion and cohesion between the liquid metal nanoparticles and the substrate and between the particles are enhanced due to the interaction of the hydrophilic groups, so that the local stress concentration is enhanced, making it easier for the discrete particles to break and fuse to form a conductive path (this process is referred to as "activation" or "activated fusion" in this article). This process maintains the high quality of the microscale liquid metal pattern defined by the photolithography, while transforming it from an insulator to a high conductor ( Fig.12 This strategy is applicable to liquid metal nanoparticles of various sizes, from 250 nanometers to several micrometers ( Fig.13 ), and exhibited good activation uniformity ( Fig.14 ) and the applicability of various reverse peeling elastomers ( Fig.15 ). Liquid metal patterns activated by the plasma-assisted liquid metal self-activation (PLASMA) method, even when composed of nanoscale liquid metal nanoparticles, exhibit conductivity higher than 10,000 S / cm, and for 500-nanometer-sized nanoparticles (NPs), the maximum conductivity can reach 22,000 S / cm, close to the level of bulk liquid metal. This is 4 to 10 times higher than the conductivity of previously reported submicron-sized liquid metal nanoparticles after activation under external stimulation.
[0044] To understand the key role of the plasma step, X-ray photoelectron spectroscopy (XPS) measurements and 180° peel tests were performed on liquid metal nanoparticles (NPs) before and after plasma treatment. Fig.16 and Fig.17 After plasma treatment, the peak area of the aliphatic CH / CC bond (284.8 eV) in the core level XPS spectrum of Cls ("Cls" usually refers to the characteristic energy level measured in the photoelectron spectroscopy (XPS) of the element "carbon (C)") decreased significantly, while the peaks corresponding to higher oxidation states (CCO at 286.0 eV, CO at 287.3 eV, and O- C=O at 288.4 eV) increased, indicating that during plasma exposure, the hydrophilic modification caused by active oxygen species ( Fig.13 ). These polar groups enhance the interparticle cohesion through dipole-dipole interactions. In addition, XPS and SEM analysis revealed that the block copolymer ligands were gradually etched by plasma, which further facilitated the sintering of liquid metal NPs.
[0045] The change in interfacial adhesion with the change in plasma duration is reflected in the peel force of the 180° peel test. When the plasma duration increased from 0 to 20 seconds, the peeling mainly occurred at the interface between the liquid metal NPs and the donor substrate. The peeling force increased by 3 times and reached a maximum value, marking the enhancement of interfacial adhesion due to the plasma-induced hydrophilic functionalization of the particles and Si / SiO2 substrate. However, when the plasma treatment time exceeded 20 seconds, the peeling force decreased and the peeling shifted to the separation between the liquid metal NPs, which was inferred from the residual liquid metal NPs on the donor substrate after the elastomer peeling. This suggests that too long plasma exposure may lead to excessive adhesion between the particles and the substrate.
[0046] The inventors also found that the conductivity trend of liquid metal nanoparticles activated by plasma-assisted liquid metal self-activation (PLASMA) is related to the synergistic effect of inter-particle cohesion and interfacial adhesion under the influence of plasma duration. The conductivity depends largely on the duration of the plasma, which should ideally be between 10 and 40 seconds. Without plasma treatment, the liquid metal nanoparticle pattern transferred to the elastomer substrate is still insulating, even for micron-sized particles. In contrast, only 2 seconds of plasma treatment can transform submicron-sized liquid metal nanoparticles from insulators to conductors with moderate conductivity. As the plasma duration increases (up to 10 seconds), the conductivity continues to increase, which is attributed to the enhancement of particle cohesion and adhesion caused by hydrophilic functionalization. However, further extending the plasma duration (e.g., 300 seconds) will lead to a decrease in conductivity, which may be due to incomplete transfer of liquid metal nanoparticles.
[0047] To this end, the inventors conducted finite element analysis (FEA) simulations to explore the effect of adhesion on the activation of liquid metal nanoparticles ( Fig.18 and Fig.19 ). The activation process is modeled as an inelastic self-similar peeling, combined with plastic bending deformation in the peeling area to release energy. The stress is most concentrated near the peeling line, resulting in local fracture of the liquid metal NPs oxide layer, and dissipates rapidly with increasing distance from the peeling line. The inventors' FEA model also shows that the maximum stress increases with increasing local peeling angle, which means that stronger adhesion increases the probability of liquid metal NP activation. "The conductive patterns prepared using liquid metal photoresist also exhibit good single and cyclic stretching capabilities ( Fig. 20 ).
[0048] The above is the research conducted by the inventor on the liquid metal photoresist composition, preparation method, patterning method based on the liquid metal photoresist composition, and plasma-assisted liquid metal self-activation strategy proposed in the present invention.
[0049] To realize the concept of the present invention, the first aspect of the present invention provides an embodiment of a liquid metal photoresist composition, the liquid metal photoresist composition comprises a solid substance and a solvent; wherein, The solid material comprises ligand-modified liquid metal nanoparticles and a photosensitive crosslinker; the liquid metal comprises gallium or a gallium-based alloy; the ligand modifying the liquid metal comprises: at least one of amphiphilic polymers; wherein the molar ratio of the hydrophilic structural unit (also referred to as a hydrophilic group in other places of the present invention) to the lipophilic structural unit (lipophilic group) in the amphiphilic polymer is (0.001-0.1):1; the photosensitive crosslinker comprises at least one of a double-end substituted diaziridine crosslinker, a double-end substituted perfluoroazide crosslinker, a double-end substituted benzophenone crosslinker, and a double-end substituted diaziridine crosslinker; The solvent includes at least one of hydrocarbons, ketones, alcohols, ethers, and alkylamides.
[0050] Compared with the liquid metal photoresist in the prior art which requires up to 6 components, the liquid metal photoresist composition in the present invention has a simple formula and only requires the ligand-modified liquid metal nanoparticles and the photosensitive crosslinker to be dispersed together in a solvent, thus greatly simplifying the composition.
[0051] Furthermore, in the present invention, the liquid metal photoresist composition comprises 60 wt % to 95 wt % of ligand-modified liquid metal nanoparticles and 5 wt % to 40 wt % of a photosensitive crosslinker, based on the mass of the solute.
[0052] In some embodiments of the present invention, the liquid metal is a Ga-In-based, Ga-In-Sn-based low temperature alloy or a Ga-based low temperature alloy containing other metal additives.
[0053] In the present invention, the amphiphilic polymer can be a random copolymer or a block copolymer, and the amphiphilic polymer includes at least one of polymethyl methacrylate-polyacrylic acid, polymethyl methacrylate-polymethacrylic acid, styrene-isoprene-styrene block copolymer with hydrophilic modification, styrene-butadiene-styrene block copolymer with hydrophilic modification, polypropylene-polyacrylic acid, polyethylene-polyacrylic acid, polyethylene glycol-polystyrene, polyvinyl alcohol-polypropylene, polyethylene glycol-polypropylene, and polyvinyl alcohol-polystyrene. As long as the molar ratio of the hydrophilic structural unit to the lipophilic structural unit is (0.001-0.1): 1. In some preferred embodiments of the present invention, the molar ratio of the hydrophilic structural unit to the lipophilic monomer unit is (0.004-0.064): 1.
[0054] In some preferred embodiments of the present invention, the amphiphilic polymer is a block copolymer.
[0055] In the present invention, the hydrophilic structural unit constituting the amphiphilic polymer refers to a unit containing polar groups such as -COOH, -OH, -SH, and -NH2, and the lipophilic structural unit constituting the amphiphilic polymer refers to a non-polar unit having at least one carbon atom.
[0056] In some preferred embodiments of the present invention, the molar ratio (or mass ratio, either one can be selected) of the hydrophilic structural unit to the lipophilic structural unit is 0.01:1.
[0057] In the present invention, the weight average molecular weight of the amphiphilic polymer is in the range of 5,000-100,000, preferably 25,000-30,000.
[0058] In the present invention, “amphiphilic polymer-modified liquid metal nanoparticles” or “ligand-modified liquid metal nanoparticles” may also be referred to as “liquid metal nanoparticles” for short.
[0059] In the present invention, the average particle size of the liquid metal nanoparticles ranges from about 190 nm to about 1000 nm. After the average particle size is determined, the particle size of the liquid metal nanoparticles prepared each time is expected to be normally distributed with the average particle size as the desired size.
[0060] In some preferred embodiments of the present invention, the average particle size of the liquid metal nanoparticles ranges from about 400 nm to about 600 nm.
[0061] In the present invention, the structure of the photosensitive crosslinking agent molecule is: two photosensitive groups with the same molecular structure are connected by a straight or branched alkyl group or its derivatives (including straight or branched octyl, nonyl, decyl or their derivatives) having more than one carbon atom.
[0062] In some further preferred embodiments of the present invention, one or more hydrogen atoms in the alkyl derivative in the fragment bridged by the photosensitive crosslinker are replaced by at least one of -OH, -COOH, -COO-, -OCOO-, -COOCH3, -COCl, -NH3, -NH2-, -N=C=O, -CHO, -O, -S, phenyl, epoxy and halogen groups.
[0063] In the present invention, the photosensitive group in the photosensitive crosslinking agent includes at least one of diaziridine, perfluorophenylazide, benzophenone and diaziridine.
[0064] In the present invention, the cross-linking principle of the photosensitive cross-linking agent is that the carbon carbene generated by the photosensitive groups at both ends under the irradiation of ultraviolet light realizes the X-H (X=C, N) insertion reaction with the lipophilic structural unit in the amphiphilic polymer on the surface of the liquid metal nanoparticles to generate new covalent bonds, thereby making the liquid metal nanoparticles interconnected network.
[0065] In the present invention, the wavelength of ultraviolet light is generally 275-365nm.
[0066] In some preferred embodiments of the present invention, the wavelength of the ultraviolet light is 275-285 nm.
[0067] In the present invention, the irradiation intensity of ultraviolet light is 1000 mJ / cm 2 -5000 mJ / cm 2 .
[0068] In some preferred embodiments of the present invention, the irradiation intensity of the ultraviolet light is 1000-3000 mJ / cm 2 .
[0069] In some preferred embodiments of the present invention, the mass ratio of amphiphilic polymer-modified liquid metal nanoparticles: photosensitive crosslinking agent: solvent in the liquid metal photoresist composition is 100:5-10:1000-1500.
[0070] In the present invention, the solvent includes at least one of hydrocarbons, ketones, alcohols, ethers, and alkylamides.
[0071] In some preferred embodiments of the present invention, the solvent includes at least one of toluene, dimethylformamide, o-xylene, m-xylene, p-xylene, chlorobenzene and methanol.
[0072] The second aspect of the present invention further provides an embodiment of a patterning method based on the above-mentioned liquid metal photoresist, and the patterning method of the liquid metal photoresist comprises the following steps: Step (a), performing monolayer modification on a substrate; Step (b), spin coating the liquid metal photoresist on the substrate to obtain a liquid metal nanoparticle film; Step (c), exposing the liquid metal nanoparticle film by a maskless laser direct writing system; Step (d), developing the liquid metal nanoparticle film in a developer, and drying to obtain a patterned liquid metal photoresist.
[0073] In some preferred embodiments of the present invention, the substrate is a silicon / silicon dioxide wafer, and the monolayer is an octadecyltrichlorosilane (OTS) monolayer.
[0074] In some preferred embodiments of the present invention, the process conditions of the above patterning method are: 1) Cast a 1-3 mmol / L octadecyltrichlorosilane trichloroethylene solution onto a UV / ozone cleaned silicon / silicon dioxide wafer to cover the entire surface, leave it for 5-10 seconds, and then spin coat it at 3000-4000 rpm. After spin coating, place the substrate in a sealed container with a vial of ammonium hydroxide solution (28-30% aqueous solution) at room temperature for 10-18 hours. Remove the substrate and rinse it with deionized water and ultrasonicate it in toluene to remove the octadecyltrichlorosilane.
[0075] 2) Spin coating speed is 3000~5000 rpm, spin coating for 10~20 seconds; 3) Exposure conditions: laser center wavelength 365 nm~375 nm, exposure dose: 1000~4000 mJ / ; 4) The developing conditions are: the developing solution is toluene, and the developing time is 60 s~300 s.
[0076] A third aspect of the present invention provides an embodiment of a method for preparing a liquid metal photoresist composition, the method for preparing the liquid metal photoresist composition comprising the following steps: Step 1, preparing liquid metal nanoparticles modified by an amphiphilic polymer: mixing liquid metal and an amphiphilic polymer in a solvent, wherein the mass ratio of the liquid metal: the amphiphilic polymer: the solvent is 100: 0.5-6: 500-2000, and then performing a first ultrasound to obtain a solvent dispersion of the liquid metal nanoparticles modified by the amphiphilic polymer; In some preferred embodiments of the present invention, the mass ratio of liquid metal:amphiphilic polymer:solvent is 100:1-3:1000-1500.
[0077] Step 2: Add a photosensitive crosslinker and a solvent to the ligand-modified liquid metal nanoparticle solvent dispersion, and then use a second ultrasonic mixing to obtain a liquid metal photoresist composition. The composition of the liquid metal photoresist composition is amphiphilic polymer modified liquid metal nanoparticles: photosensitive crosslinker: solvent mass ratio of 100:5-40:500-2000.
[0078] In some preferred embodiments of the present invention, the mass ratio of amphiphilic polymer-modified liquid metal nanoparticles: photosensitive crosslinking agent: solvent is 100:5-10:1000-1500.
[0079] In some preferred embodiments of the present invention, in step 1, the first ultrasonic time is 15 min-360 min. More preferably, the first ultrasonic time is 50 min-200 min.
[0080] In some preferred embodiments of the present invention, in step 1, the ultrasonic power of the first ultrasound is 280W-330 W. More preferably, the ultrasonic power of the first ultrasound is 300W-330W.
[0081] In some preferred embodiments of the present invention, in step 1, the first ultrasound is performed at a temperature of -10°C to 0°C. More preferably, the first ultrasound is performed at a temperature of -10°C to -5°C.
[0082] In some preferred embodiments of the present invention, in step 2, the second ultrasonic time is 10 s-60 s. More preferably, the second ultrasonic time is 10 s-30 s.
[0083] In some preferred embodiments of the present invention, in step 2, the ultrasonic power of the second ultrasound is 100 W-150 W. More preferably, the ultrasonic power of the second ultrasound is 120 W-150 W.
[0084] In some preferred embodiments of the present invention, in step 2, the second ultrasound is performed at a temperature of 0° C. to 25° C. More preferably, the second ultrasound is performed at a temperature of 15° C. to 25° C.
[0085] In the preparation method of the liquid metal photoresist composition of the present invention, liquid metal nanoparticles with a size range of about 200 nanometers to about 1 micron are synthesized by adjusting process parameters such as ultrasonic time, power and temperature, and a uniform liquid metal nanoparticle film can also be formed by simple solution processing without the need for wetting metal or complex printing equipment.
[0086] In the present invention, "substrate" refers to a material on which a photoresist is coated and on which a photoresist film is formed.
[0087] In the present invention, the material of the "substrate" is generally a silicon-containing material, such as silicon (Si), silicon dioxide (SiO2), silicon (Si) or silicon dioxide (SiO2) modified by a monolayer (the monolayer used may be octadecyltrichlorosilane, dodecylphosphonic acid, trimethoxysilane, etc.), etc.
[0088] In the present invention, the adhesion energy between the liquid metal photoresist composition and the substrate is 0.01-0.1 N / mm. In the present invention, the adhesion is tested by the 180° peeling method (the experimental process is based on "GB / T 2790-1995 Adhesive 180° Peel Strength Test Method").
[0089] The fourth aspect of the present invention also provides an embodiment of a method for combining plasma-assisted liquid metal self-activation, comprising the following steps: S1, preparing a patterned liquid metal photoresist on a silicon substrate; S2, plasma treating the patterned liquid metal photoresist; S3, pouring the elastomer solution on the silicon base; S4, evaporating the solvent in the elastomer solution to obtain an elastomer film; S5. Peeling the elastomer film off the silicon substrate to obtain a liquid metal conductive pattern attached to the elastomer film.
[0090] In step S1, the silicon base is the "substrate" mentioned above. In step S2, the "plasma treatment" can be atmospheric plasma treatment, microwave plasma treatment, high-frequency plasma treatment, stimulated plasma treatment, DC arc plasma treatment, etc., and atmospheric plasma treatment is preferably used in the present invention. In step S3, the elastomer solution refers to a liquid or colloidal mixture formed by dissolving an elastomer (such as polyurethane, natural rubber, synthetic rubber, etc.) in an appropriate solvent, which has good fluidity and permeability. There are many types of elastomers on the market, such as SG80A, SG85A, H1221, H1052, H1062 and 126S. These elastomer types can be obtained commercially and will not be repeated here. In step S5, the elastomer film is peeled off from the silicon base, and the peeling force applied manually is given priority, but it is not limited to mechanical operation.
[0091] As described above, in the combined plasma-assisted liquid metal self-activation method provided by the present invention, hydrophilic groups are introduced into the liquid metal nanoparticles and the silicon base by plasma treatment of the patterned liquid metal photoresist, and then the elastomer solution is directly poured on the micro-scale liquid metal pattern. While peeling the elastomer film from the silicon base, due to the interaction of the hydrophilic groups, the adhesion and cohesion between the liquid metal nanoparticles and the silicon base and between the liquid metal nanoparticles and the particles are enhanced, so that the local stress concentration is enhanced, and it is easier to make the discrete particles break and fuse to form a conductive path (this process is referred to as "activation" in this article). This process maintains the high quality of the micro-scale liquid metal pattern defined by lithography, while transforming it from an insulator to a high conductor.
[0092] Furthermore, in step S2 of the present invention, the patterned liquid metal photoresist is preferably placed in an air environment plasma cleaning machine for plasma treatment, the power of the air environment plasma cleaning machine is above 100 W, and the plasma treatment time is above 2 seconds.
[0093] Still further preferably, the power of the air environment plasma cleaning machine is 100-200 W, and the plasma treatment time is 10 seconds to 40 seconds.
[0094] Furthermore, step S1 of the present invention comprises: S11, preparing ligand-modified liquid metal nanoparticles: mixing liquid metal and ligand in a solvent, and then performing a first ultrasonic treatment to obtain ligand-modified liquid metal nanoparticles, wherein the liquid metal includes gallium or a gallium-based alloy, and the ligand includes at least one of amphiphilic polymers; S12, adding a photosensitive crosslinking agent and a solvent to the ligand-modified liquid metal nanoparticles, and then uniformly mixing them by a second ultrasonic method to obtain a liquid metal photoresist composition; S13, monolayer modification on silicon substrate; S14, spin coating the liquid metal photoresist composition obtained in step S12 on the substrate to obtain a liquid metal nanoparticle film; S15, exposing the liquid metal nanoparticle film; S16, developing the liquid metal nanoparticle film in a developer, and drying to obtain a patterned liquid metal photoresist.
[0095] Furthermore, in step S11, the mass ratio of liquid metal: amphiphilic polymer is no more than 100:6; in step S12, the final mass ratio of amphiphilic polymer modified liquid metal nanoparticles: photosensitive crosslinker: solvent is 100:5-40:500-2000; in step S15, the liquid metal nanoparticle film is exposed by a maskless laser direct writing system.
[0096] Furthermore, the molar ratio of the hydrophilic structural unit to the lipophilic structural unit in the amphiphilic polymer is (0.001-0.1):1; the photosensitive crosslinker includes at least one of a double-ended bis-aziridine crosslinker, a double-ended perfluoroazide crosslinker, and a double-ended benzophenone crosslinker; and the solvent includes at least one of hydrocarbons, ketones, alcohols, ethers, and alkylamides.
[0097] The amphiphilic polymer includes at least one of polymethyl methacrylate-polyacrylic acid, polymethyl methacrylate-polymethacrylic acid, hydrophilically modified styrene-isoprene-styrene block copolymer, hydrophilically modified styrene-butadiene-styrene block copolymer, polypropylene-polyacrylic acid, polyethylene-polyacrylic acid, polyethylene glycol-polystyrene, polyvinyl alcohol-polypropylene, polyethylene glycol-polypropylene, and polyvinyl alcohol-polystyrene; The photosensitive crosslinking agent molecule has photo-crosslinking group molecules at both ends, and the photo-crosslinking groups at both ends include at least one of an azido group, a diaziridine group, and a benzophenone group.
[0098] In addition, in the plasma-assisted liquid metal self-activation method provided by the present invention, process parameters such as ultrasonic time, power and temperature have a great influence on the quality of the formed pattern. Specifically, in step S11, the time of the first ultrasound is 15 min-360 min, the ultrasonic power of the first ultrasound is 280 W-330 W, and the first ultrasound is performed at a temperature of -10°C to 0°C; in step S12, the time of the second ultrasound is 10 s-60 s, the ultrasonic power of the second ultrasound is 100 W-150 W, and the second ultrasound is performed at a temperature of 0°C to 25°C.
[0099] The fourth aspect of the present invention also provides the use of the above-mentioned liquid metal photoresist composition or the preparation method of the liquid metal photoresist composition or the patterning method based on the liquid metal photoresist composition or the combination of the plasma-assisted liquid metal self-activation method in the manufacture of stretchable electronic devices or stretchable electronic systems. In some embodiments of the present invention, the stretchable electronic device or stretchable electronic system includes at least one of a soft robot, an implantable electronic device, and an electronic skin.
[0100] The present invention will be described in detail below by way of examples and comparative examples, but the present invention is not limited thereby. In the following examples and comparative examples, unless otherwise specified, the materials used can be obtained commercially. Example 1
[0101] This embodiment is used to illustrate the liquid metal photoresist composition of the present invention and its preparation method and application.
[0102] A method for preparing a liquid metal photoresist composition comprises the following steps: Step 1, preparing ligand-modified liquid metal nanoparticles: 100 mg of gallium and 6 mg of polymethyl methacrylate-polyacrylic acid block copolymer (weight average molecular weight of 15000 g / mol, ratio of hydrophilic structural unit methacrylic acid to lipophilic structural unit methyl acrylate of 0.006:1) were mixed in 8000 mg of toluene, and then subjected to a first ultrasound, wherein the first ultrasound time was 50 min, the ultrasound power was 330 W, and the temperature was -5°C, to obtain ligand-modified liquid metal nanoparticles (liquid metal nanoparticles with a particle size range of 250 nm-750 nm); Step 2: Add 20 mg of a double-end substituted perfluoroazide crosslinker to the ligand-modified liquid metal nanoparticles, and then mix them evenly using a second ultrasonic treatment, wherein the second ultrasonic treatment lasts for 30 s, the ultrasonic power is 120 W, and the temperature is 15° C. to obtain a liquid metal photoresist composition. Example 2
[0103] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the raw materials in step (1) included: 100 mg of gallium, 30 mg of hydrophilically modified styrene-isoprene-styrene block copolymer (weight average molecular weight of 20,000, ratio of hydrophilic structural unit hydroxylated butadiene to lipophilic structural unit styrene of 0.04:1) and a double-end substituted diaziridine crosslinking agent. Example 3
[0104] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the raw materials in step (1) included: 100 mg of gallium, 50 mg of polyethylene-polyacrylic acid copolymer (weight average molecular weight of 12000, ratio of hydrophilic structural unit polyacrylic acid to lipophilic structural unit polyethylene of 0.1:1) and 12 g of dimethyl sulfide. Example 4
[0105] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the raw materials in step (1) included: 0.8 g of gallium-indium alloy (wherein the gallium content was 75 wt % and the indium content was 25 wt %), 30 mg of polyethylene-polyethylene glycol block polymer (with a weight average molecular weight of 5000 and a ratio of hydrophilic structural unit polyethylene glycol to lipophilic structural unit polyethylene of 0.02:5) and 10 g of chlorobenzene. Example 5
[0106] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the raw materials in step (1) included: 1.5 g of a gallium-indium-tin alloy (wherein the gallium content was 60 wt %, the indium content was 20 wt %, and the tin content was 20 wt %), polyethylene glycol-polypropylene (weight average molecular weight was 5000, and the ratio of the hydrophilic structural unit polyethylene glycol to the lipophilic structural unit polypropylene was 0.02:5) and 10 g of chlorobenzene. Example 6
[0107] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the first ultrasonication in step (1) was 200 min. Example 7
[0108] The liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the second ultrasonication in step (2) was 10 s. Example 8
[0109] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the first ultrasonication in step (1) was 15 min. Example 9
[0110] A liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the first ultrasonication in step (1) was 360 min. Example 10
[0111] The liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the second ultrasonication in step (2) was 60 s.
[0112] Comparative Example 1 The liquid metal photoresist composition was prepared according to the method of Example 1, except that the raw material composition in step (1) did not contain the ligand polymethyl methacrylate-polyacrylic acid copolymer.
[0113] Comparative Example 2 The liquid metal photoresist composition was prepared according to the method of Example 1, except that the ligand in the composition of the raw materials in step (1) was polymethyl methacrylate instead of an amphiphilic polymer.
[0114] Comparative Example 3 A liquid metal photoresist composition was prepared according to the method of Example 1, except that the first ultrasonic treatment time in step (1) was 10 min.
[0115] Comparative Example 4 A liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the first ultrasonication in step (1) was 480 min.
[0116] Comparative Example 5 The liquid metal photoresist composition was prepared according to the method of Example 1, except that the time of the second ultrasonication in step (1) was 1 s.
[0117] Test Case The liquid metal photoresist compositions in the examples and comparative examples were tested as follows: 1. Film density test: The test method is as follows: using photoresists prepared under different process conditions, prepare thin films under the same substrate and spin coating process conditions, observe the film surface with a scanning electron microscope, count the number and size of pores on the film surface, calculate the porosity per unit area, and verify the film density.
[0118] 2. Film adhesion test: the test method is as follows: using photoresists prepared under different process conditions, prepare thin films under the same substrate and spin coating process conditions, perform a 180° peel test using a polyurethane elastic tape, and calculate the adhesion force using a linear elastic body model without plastic deformation. The degree of adhesion is evaluated by the size of the adhesion force.
[0119] 3. Photolithography accuracy test. The test method is as follows: using photoresists prepared under different process conditions, photolithography is used to prepare stripes with different line widths and line spacings under the same exposure energy density. The minimum line width and line spacing obtained are taken as the photolithography accuracy that can be achieved by the photoresist.
[0120] Table 1
[0121] Result analysis: It can be seen from the results in Table 1 that the liquid metal photoresist composition prepared in the embodiment of the present invention has low porosity and good adhesion, the minimum line width can reach about 2μm, and the line spacing can reach about 5μm, while Comparative Examples 1 and 2 cannot produce photolithographic patterns, so there is no line width and line spacing.
[0122] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0123] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0124] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for self-activation of liquid metal by plasma assistance, characterized in that: The following steps are involved: S1, preparing a patterned liquid metal photoresist on a silicon substrate; S2, plasma treating the patterned liquid metal photoresist; S3, pouring the elastomer solution on the silicon base; S4, evaporating the solvent in the elastomer solution to obtain an elastomer film; S5. Peeling the elastomer film off the silicon substrate to obtain a liquid metal conductive pattern attached to the elastomer film.
2. The method for self-activation of liquid metal by plasma-assisted liquid metal according to claim 1, characterized in that: In step S2, the patterned liquid metal photoresist is placed in an air environment plasma cleaning machine for plasma treatment, the power of the air environment plasma cleaning machine is above 100 W, and the plasma treatment time is above 2 seconds.
3. The method for self-activation of liquid metal by plasma assistance according to claim 2, characterized in that: The power of the air environment plasma cleaning machine is 100-200W, and the plasma treatment time is 10 seconds to 40 seconds.
4. The method for self-activation of liquid metal by plasma assistance according to claim 1, characterized in that: Step S1 includes: S11, preparing ligand-modified liquid metal nanoparticles: mixing liquid metal and ligand in a solvent, and then performing a first ultrasonic treatment to obtain ligand-modified liquid metal nanoparticles, wherein the liquid metal includes gallium or a gallium-based alloy, and the ligand includes at least one of amphiphilic polymers; S12, adding a photosensitive crosslinking agent and a solvent to the ligand-modified liquid metal nanoparticles, and then uniformly mixing them by a second ultrasonic method to obtain a liquid metal photoresist composition; S13, monolayer modification on silicon substrate; S14, spin coating the liquid metal photoresist composition obtained in step S12 on the substrate to obtain a liquid metal nanoparticle film; S15, exposing the liquid metal nanoparticle film; S16, developing the liquid metal nanoparticle film in a developer, and drying to obtain a patterned liquid metal photoresist.
5. The method for self-activation of liquid metal by plasma assistance according to claim 4, characterized in that: In step S11, the mass ratio of liquid metal: amphiphilic polymer is no more than 100:6; in step S12, the final mass ratio of amphiphilic polymer modified liquid metal nanoparticles: photosensitive crosslinker: solvent is 100:5-40:500-2000; in step S15, the liquid metal nanoparticle film is exposed by a maskless laser direct writing system.
6. The method for self-activation of liquid metal by plasma assistance according to claim 4, characterized in that: The molar ratio of the hydrophilic structural unit to the lipophilic structural unit in the amphiphilic polymer is (0.001-0.1):1; the photosensitive crosslinking agent includes at least one of a double-end substituted diaziridine crosslinking agent, a double-end substituted perfluoroazide crosslinking agent, and a double-end substituted benzophenone crosslinking agent; the solvent includes at least one of hydrocarbons, ketones, alcohols, ethers, and alkylamides.
7. The method for self-activation of liquid metal by plasma assistance according to claim 4, characterized in that: The amphiphilic polymer includes at least one of polymethyl methacrylate-polyacrylic acid, polymethyl methacrylate-polymethacrylic acid, hydrophilically modified styrene-isoprene-styrene block copolymer, hydrophilically modified styrene-butadiene-styrene block copolymer, polypropylene-polyacrylic acid, polyethylene-polyacrylic acid, polyethylene glycol-polystyrene, polyvinyl alcohol-polypropylene, polyethylene glycol-polypropylene, and polyvinyl alcohol-polystyrene; and / or, The photosensitive crosslinking agent molecule has photo-crosslinking group molecules at both ends, and the photo-crosslinking groups at both ends include at least one of an azido group, a diaziridine group, and a benzophenone group.
8. The method for self-activation of liquid metal by plasma assistance according to claim 4, characterized in that: In step S11, the first ultrasound duration is 15 min-360 min; and / or In step S11, the ultrasonic power of the first ultrasound is 280W-330W; and / or In step S11, the first ultrasound is performed at a temperature of -10°C to 0°C; and / or In step S12, the second ultrasound duration is 10 s-60 s; and / or In step S12, the ultrasonic power of the second ultrasound is 100 W-150 W; and / or In step S12, the second ultrasound is performed at a temperature of 0°C to 25°C.
9. Application of the plasma-assisted liquid metal self-activation method according to any one of claims 1 to 8 in the manufacture of stretchable electronic devices or stretchable electronic systems.
Citation Information
Cited By
Method for inducing fusion sintering of liquid metal micro-nano liquid drops by utilizing Malangori effect
CN121267177A